Violence due to gender bias and self-care practices in transgender women living in Bogotá - Beltran, Jenny Amparo Lozano (Saúde e Sociedade, 2024)
Goals. To know the self-care practices of transgender women in the city of Bogotá, in response to violence due to gender bias arising from the transformation process. Methodology. Qualitative approach to 5 transgender women and 5 people accompanying the process, through semi-structured, recorded, transcribed and analyzed interviews. Results and conclusions. In the discourse of transgender women, experiences associated with violence due to gender bias, experienced during the transformation process, are repeated. From this, various self-care practices were found, created and adapted to protect their health. It is considered necessary to implement public health policies that allow the visibility of diverse identities, promoting the protection and guarantee of the rights of transgender women.